1971
DOI: 10.1073/pnas.68.12.2954
|View full text |Cite
|
Sign up to set email alerts
|

Slow Joining of Newly Replicated DNA Chains in DNA Polymerase I-Deficient Escherichia coli Mutants

Abstract: In Escherichia coli mutants deficient in DNA polymerase I, newly -replicated short DNA is joined at about 10% of the rate in the wild-type strains. It is postulated that DNA polymerase I normally functions in filling gaps between the nascent short segments synthesized by the replication complex. Possible implications of the finding are discussed in relation to other abnormal properties of these mutants.Mutants of Escherichia coli deficient in DNA polymerase I (pob mutants) (1-3) grow normally. These mutants, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
67
0

Year Published

1972
1972
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(71 citation statements)
references
References 33 publications
4
67
0
Order By: Relevance
“…This interpretation was confirmed in polA mutants, deficient in DNA polymerase I (13)(14)(15) and with DNA ligase mutants (11,16,17). Not only was all DNA synthesized in LMW pieces in polA and ligA mutants, but it then stayed short for some time, indicating that both DNA polymerase I and DNA ligase are the maturation functions.…”
supporting
confidence: 51%
See 1 more Smart Citation
“…This interpretation was confirmed in polA mutants, deficient in DNA polymerase I (13)(14)(15) and with DNA ligase mutants (11,16,17). Not only was all DNA synthesized in LMW pieces in polA and ligA mutants, but it then stayed short for some time, indicating that both DNA polymerase I and DNA ligase are the maturation functions.…”
supporting
confidence: 51%
“…With this evidence, Okazaki and colleagues proposed a discontinuous model of DNA replication (Fig. 1C) in which both the lagging and the leading strands are synthesized in short fragments and maturated later into HMW species by the combined action of DNA polymerase I (plus RNase H) and DNA ligase (15,19).…”
mentioning
confidence: 99%
“…Evidence has accumulated that DNA is replicated by a discontinuous mechanism involving systhesis and joining of short DNA units (1)(2)(3)(4)(5)(6)(7)(8). Little is known, however, about the mechanism of creation of the short DNA chains.…”
mentioning
confidence: 99%
“…These mutants are abnormally sensitive to ultraviolet irradiation and to the alkylating agent methyl methanesulfonate, and show retarded joining of the 10S "Okazaki fragments" (6)(7)(8). A recent analysis of partially purified fractions derived from..several of the polA mutants has demonstrated that although they contain much reduced levels of DNA polymerase I activity the 5' --3' exonuclease associated with the polymerase I is present in nearly normal amounts (9).…”
mentioning
confidence: 99%